Care Bears (Caries Pervention Bears): Gummy Bears from Mangosteen Peel as A Preventive Measure Against Dental Caries for Child - Alya Iffah Nur Kamila; Aria Nalini Farzana; Yesi Yuliani (Jurnal Integrasi Sains dan Quran, 2022)
Since the COVID-19 pandemic, people wash their hands twice as often (64%) as they brush their teeth (31%). 2 out of 5 adults say they don't brush their teeth all day long. This habit is 7 times more likely to be imitated by children (kemkes.go.id, 2021). Globally, it is estimated that more than 530 million children suffer from primary dental caries (WHO, 2020). In general, children tend to dislike drugs and more likely to like sweets. The purpose of this study was to determine the effectiveness of Care Bears in preventing dental caries for child. This type of research is a qualitative descriptive study where the focus of the description is on the manufacture of gummy bears as a preventive measure against dental caries which generally infect children due to poor eating and brushing habits. The effectiveness of gummy bears’ prevention is based on the results of the respondents' acceptance and the antibacterial activity test on bacterial preparations in dental plaque. The results showed that Care Bear is quite acceptable by children and has preventive ability of bacteria. We hope that in the future this product can be mass produced so that it can help many children from dental caries.